STRATEGI POLITIK PAKUBUWANA VI MELAWAN KOLONIAL BELANDA TAHUN 1823 – 1830 - Sukrismiyati, Sukrismiyati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
The purpose of this research are to know: (1) Political conditions in Surakarta palace before and during the reign of Pakubuwana VI, (2) Political strategy of Pakubuwana VI against Dutch colonial, (3) End of the match of Pakubuwana VI against Dutch colonial, (4) Implications of political strategy Pakubuwana VI in educationThis research uses historical method. The steps taken by the historical method there are four stages of activities: heuristic, criticism, interpretation and historiography. Data sources uses are written sources which archives, books, magazines and newspapers. Data collection techniques used is the technique literature. Analysis of the data used is the analysis of historical analysis that prioritizes sharpness in interpretating the facts of history.Based on the research done, it can be concluded that: (1) Political conditions in Surakarta palace was heavily influenced by the Dutch colonial. The Netherlands also apply political divide et empera that aims to disrupt the stability of Surakarta palace. Relationship between Surakarta palace with colonial government created in the form of agreements. One of the important agreement is an agreement in 1749 that the contents of the devolution of authority to the VOC. (2) Conflict between Pakubuwana VI with the Dutch colonial government is due to the agreements made by the predecessor. Among them was an agreement in 1677, 1705, and 1749. All agreements are detrimental to the palace of Surakarta and limiting power Pakubuwana VI. (3) In the Java War Pakubuwana VI assist Prince Diponegoro. On the one hand Pakubuwana required to provide assistance to the Netherlands because of the bond agreement. For the Pakubuwana VI Prince Diponegoro recommend a relief to quietly. Some of the strategies used include Mimis Kencana tactics, tactics Candrodimuko, secret meetings and Guerrilla War. (4) At the end of the War of Javanese prince Diponegoro was arrested and exiled by the Dutch to Manado, and Pakubuwana VI exiled to Ambon on 8 July 1830. Pakubuwana VI died on July 5, 1849. (5) Implications of political strategy Pakubuwana VI in education, that can be used as literature in political education. Due to the political education not only include material about politics but also economics and history.